The conflict between the Angevins and the Byzantines in Morea in 1267-1289: A Late Byzantine endemic war - WILSKMAN, Juho (Byzantina Symmeikta, 2012)
This article attempts to reconstruct a late Byzantine low-level war, namely the conflict in the Morea during 1267-1289, which took place between the Angevins and their vassal, the Principality of Achaia, on the one side, and the Byzantines on the other side. This conflict offers a case of relatively well-documented late Byzantine low-level warfare. Special attention is given to the economic and demographic consequences of war for Morea, for the building of fortresses, and to the idea put forward in previous research that the war in Morea needlessly took resources away from the defense of Anatolia – thus contributing to the loss of the area to the Turks.